Preliminary Study of Euryale ferox Salisb. Seed Coat as a Potential Antioxidant and Antibacterial Source - Kadu, Manali; Maknojia, Rashmin; Maharana, Subhashini (Asian Journal of Biological and Life Sciences, 2020)
Agro-industrial waste generated each year causes detrimental effects on the environment and economy, but is a rich source of bioactive compounds. These compounds when recovered have various applications in food, pharmaceutical, cosmetic and packaging industry. In the present study, Euryale ferox Salisb. seed coat was used, a waste product of Makhana processing. Different solvents were used to extract the phytochemicals, the highest extraction value was found in ethanol:water. Phytochemical analysis, total phenols, flavonoids content, antioxidant and antibacterial activity was carried out of the seed coat extract. Phytochemical screening of extracts showed presence of phenols, tannins, alkaloids, glycosides, terpenoids, steroids and flavonoids. The total phenol content and flavonoid content was found to be 50.967±0.107 GAE mg/g and 16.274±0.73 QE mg/g respectively. The antioxidant activity of the ethanol: water extract was studied by using DPPH assay and IC50 value was found to be 1.62μg/mL. Antibacterial activity was carried out using agar cup method and was determined against E. coli and S. aureus. Ethyl acetate and ethanol extract showed higher zone of inhibition as compared to the other extracts. Development of HPTLC fingerprint profile for separation of active constituents was carried out. This study indicates that Euryale ferox seed coat might be a valuable bioactive source for antioxidant and antibacterial activity.
Keywords: Antibacterial; Antioxidant; Euryale ferox Salisb.; HPTLC fingerprinting; Seed coat